Determination the Natural Radioactivity Levels at Selected Regions in Al-Najaf Governorate - M. Hasan, Nada; K. Alsaedi, Jamal; K. Alnasri, Salam; A. Abdulhasan, Ali (Al-Nahrain Journal of Science, 2021)
The natural radioactivity levels for radium (226Ra), thorium (232Th) and potassium (40K) have been determined in soil samples selected from different regions in Najaf governorate in Iraq. The samples were collected from the ground surface. Eight samples were measured by gamma ray spectroscopy using high purity germanium detector. The levels of radionuclides concentrations in selected samples 232Th, 226Ra and 40K were in the range of (2.5±0.29 to 7.7±0.52) Bq/kg (6.3±0.43 to 16.4±1.9) Bq/kg and (31.5±3.4 to 204.1±11.9) Bq/kg for, respectively. The mean Radium Equivalent Activity, External and Internal Hazard Indices, the Absorbed Dose Rate in Air and the Annual Effective Doses Equivalent were studied and found these parameter are less than the reported values. Therefore, the radioactivity in the studied area in Najaf does not pose any radiological hazard to the general public.